Modulated release from implantable ocular silicone oil tamponade drug reservoirs. Issue 8 (9th February 2018) - Cauldbeck, Helen; Le Hellaye, Maude; McDonald, Tom O.; Long, Mark; Williams, Rachel L.; Rannard, Steve P.; Kearns, Victoria R.
ABSTRACT: Complicated cases of retinal detachment can be treated with silicone oil tamponades. There is the potential for silicone oil tamponades to have adjunctive drug releasing behaviour within the eye, however the lipophilic nature of silicone oil limits the number of drugs that are suitable, and drug release from the hydrophobic reservoir is uncontrolled. Here, a radiometric technique was developed to accurately measure drug solubility in silicone oil and measure release into culture media. All‐trans retinoic acid (atRA), a lipophilic drug known to act as an anti‐proliferative within the eye, was used throughout this work. Chain‐end modification of polydimethylsiloxane with atRA produced a polydimethylsiloxane retinoate (PDMS‐atRA), which was used as an additive to silicone oil to modify the solvent environment within the silicone oil and the distribution coefficient. Blends of PDMS‐atRA and silicone oil containing different concentrations of free atRA were produced. The presence of PDMS‐atRA in silicone oil had a positive effect on atRA solubility and the longevity of release in vitro . The drug release period was independent of atRA starting concentration and dependent on the PDMS‐atRA concentration in the blend. A clinically relevant release period of atRA over 7 weeks from a silicone oil blend with PDMS‐atRA was observed. © 2018 The Authors. Journal of Polymer Science Part A: Polymer Chemistry Published by Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 938–946 Abstract : A novel polymeric additive, designed to be combined with silicone oil tamponades, was synthesised to control the release of all‐trans retinoic acid (atRA). This strategy could provide adjunctive treatment for sight‐threatening retinal detachments. Blends of this additive—a polydimethylsiloxane retinoate—were used to modify the solvent environment within the silicone oil and the distribution coefficient. A clinically relevant release period of atRA over 7 weeks was achieved.